The land administration in Penang / Badariah Khalid - Khalid, Badariah (Faculty of Law, 1984)
The Yang Di Pertuan Agong may appoint a Commissioner of Land Titles and one or more Deputy ecmmieaioners of Land titles. The Commissioner the general directions and control of all officers. Every officers appointed is deemed to be a public servant.